Brimonidine blocks glutamate excitotoxicity-induced oxidative stress and preserves mitochondrial transcription factor a in ischemic retinal injury. - Dongwook Lee (PLoS ONE, 2012)
Glutamate excitotoxicity-induced oxidative stress have been linked to mitochondrial dysfunction in retinal ischemia and optic neuropathies including glaucoma. Brimonindine (BMD), an alpha 2-adrenergic receptor agonist, contributes to the neuroprotection of retinal ganglion cells (RGCs) against glutamate excitotoxicity or oxidative stress. However, the molecular mechanisms of BMD-associated mitochondrial preservation in RGC protection against glutamate excitotoxicity-induced oxidative stress following retinal ischemic injury remain largely unknown. Here, we tested whether activation of alpha 2 adrenergic receptor by systemic BMD treatment blocks glutamate excitotoxicity-induced oxidative stress, and preserves the expression of mitochondrial transcription factor A (Tfam) and oxidative phosphorylation (OXPHOS) complex in ischemic retina. Sprague-Dawley rats received BMD (1 mg/kg/day) or vehicle (0.9% saline) systemically and then transient ischemia was induced by acute intraocular pressure elevation. Systemic BMD treatment significantly increased RGC survival at 4 weeks after ischemia. At 24 hours, BMD significantly decreased Bax expression but increased Bcl-xL and phosphorylated Bad protein expression in ischemic retina. Importantly. BMD significantly blocked the upregulations of N-methyl-D-aspartate receptors 1 and 2A protein expression, as well as of SOD2 protein expression in ischemic retina at 24 hours. During the early neurodegeneration following ischemic injury (12-72 hours), Tfam and OXPHOS complex protein expression were significantly increased in vehicle-treated retina. At 24 hours after ischemia, Tfam immunoreactivity was increased in the outer plexiform layer, inner nuclear layer, inner plexiform layer and ganglion cell layer. Further, Tfam protein was expressed predominantly in RGCs. Finally, BMD preserved Tfam immunoreactivity in RGCs as well as Tfam/OXPHOS complex protein expression in the retinal extracts against ischemic injury. Our findings suggest that systemic BMD treatment protects RGCs by blockade of glutamate excitotoxicity-induced oxidative stress and subsequent preservation of Tfam/OXPHOS complex expression in ischemic retina.